Death in Ghana: Sociocultural implications for organ transplant regulation. (March 2014) - Banyubala, Divine N.
Within the context of organ retrieval for transplantation, death remains a controversial subject. Understandably, there are concerns about the conception of death, how it is understood, clinically defined, determined and confirmed, as well as its relationship with organ retrievals and transplantation surgery. Even though these concerns have been the subject of extensive commentary from medical, legal, ethical and social perspectives, these have been made largely in the context of the developed world. The first aim of this article is to re-examine, in the Ghanaian socio-legal context, the ethico-legal controversy around the definition, determination and confirmation of death and its relationship with obtaining organs for transplant. It is hoped that this will bring a new perspective to the debate and enrich our ethico-legal discourse on the subject. Ghana is making strenuous efforts to make organ transplantation a routine surgical procedure by the end of this year, yet it has no ethical or legal framework to guide the process. A successful transplant programme will depend in part on the availability of organs from all ethically acceptable sources (deceased, living related and unrelated). This being so, the author discusses indigenous thinking around death (post-mortem personality identity renegotiation (PPIR)) and points policymakers to how they could take advantage of PPIR to promote the social utility of any organ transplantation programme in Ghana. Furthermore, I consider the nature of the role of law in defining/determining death. I consider the merits of a statutory definition of death and conclude that given the circumstances of Ghana (its socio-legal environment) and the UK experience, a judicial rather than statutory definition is workable. The overall aim of this article is to explore the need for an appropriate and comprehensive regulatory regime for the emerging sector of organ transplants in Ghana.